QUALITY ASSURANCE OF MASTER’S STUDY PROGRAM OF ENGLISH LANGUAGE EDUCATION, TEACHER TRAINING AND EDUCATION FACULTY, TANJUNGPURA UNIVERSITY - Sudarsono Sudarsono; Ikhsanuddin Ikhsanudin; Urai Salam (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
Accreditation for a study program is a must. The present study was designed to examine how far Master’s Study Program of English Language Education (S2BE) already applied its quality assurance. It was a descriptive study. The data were collected from its stakeholders covering students, alumni, alumni users, and lecturers. The instrument was a questionnaire of which the informants responded by showing their agreement to the statements. The data were analyzed with a very simple qualitative-statistical work. The research found out that the respondents rated S++ to show their strong agreement to the statements about the implementation of the quality assurance.